Entrepreneurial orientation and emotional bias in MSMEs’ financing and performance - Maria Rio Rita; Ari Budi Kristanto; Yeterina Widi Nugrahanti; Mohamad Nur Utomo (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2021)
There have been numerous studies investigating the dynamics of micro, small and medium enterprises (MSME) development. However, this research topic still offers several interesting research gaps to be explored. Accordingly, the purpose of this research is to test the effects of entrepreneurial orientation and asymmetric information that affect MSME entrepreneurs’ emotional biases, as well as the relationships between these variables and MSME’s financing and performance. Our research objects are MSMEs located in four urban villages in Salatiga City, Central Java that engage in various business sectors, such as the food and beverage, the service industry, the groceryw, and the horticulture sector. We analyze the research data with the Partial Least Square (PLS) software. The research results reveal that entrepreneurial orientation and asymmetric information positively influence MSME entrepreneurs’ emotional bias. Meanwhile, emotional bias has a significantly positive influence on financing. Finally, we also find that financing positively affects MSMEs’ performance. In sum, our study demonstrates the importance of the behavioral aspect (emotional bias) in explaining MSMEs’ performance through its indirect impact through financing.